Cardiovascular imaging: what have we learned from animal models? - Santos, Arnoldo; Fernández-Friera, Leticia; Villalba, María; López-Melgar, Beatriz; España, Samuel; Mateo, Jesús; Mota, Ruben A.; Jiménez-Borreguero, Jesús; Ruiz-Cabello, Jesús (Frontiers in Pharmacology, 2015)
Cardiovascular imaging has become an indispensable tool for patient diagnosis and follow up. Probably the wide clinical applications of imaging are due to the possibility of a detailed and high quality description and quantification of cardiovascular system structure and function. Also phenomena that involve complex physiological mechanisms and biochemical pathways, such as inflammation and ischemia, can be visualized in a nondestructive way. The widespread use and evolution of imaging would not have been possible without animal studies. Animal models have allowed for instance, i) the technical development of different imaging tools, ii) to test hypothesis generated from human studies and finally, iii) to evaluate the translational relevance assessment of in vitro and ex-vivo results. In this review, we will critically describe the contribution of animal models to the use of biomedical imaging in cardiovascular medicine. We will discuss the characteristics of the most frequent models used in/for imaging studies. We will cover the major findings of animal studies focused in the cardiovascular use of the repeatedly used imaging techniques in clinical practice and experimental studies. We will also describe the physiological findings and/or learning processes for imaging applications coming from models of the most common cardiovascular diseases. In these diseases, imaging research using animals has allowed the study of aspects such as: ventricular size, shape, global function and wall thickening, local myocardial function, myocardial perfusion, metabolism and energetic assessment, infarct quantification, vascular lesion characterization, myocardial fiber structure, and myocardial calcium uptake. Finally we will discuss the limitations and future of imaging research with animal models.